Post-operative complications and recurrence rate after treatment of bowel endometriosis: Comparison of three techniques - Alicia Hernández Gutiérrez; Emanuela Spagnolo; Ignacio Zapardiel; Rubén Garcia-Abadillo Seivane; Ana López Carrasco; Patricia Salas Bolívar; Isabel Pascual Miguelañez (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2019)
Objective: The aim of the present study was to compare post-operative complications and recurrence of three surgical techniques: segmental resection, discoid excision and nodule shaving. Study design: From January 2014 to December 2017, 143 patients who underwent segmental bowel resections for endometriosis at “La Paz” University Hospital, were enrolled and grouped by different techniques. We compared post-operative complications and recurrence rate in three groups: 76 (53%) patients underwent segmental resection (group I), 20 (14%) patients underwent discoid resection (group II) and 47 (33%) patients underwent rectal shaving (group III).Qualitative data was defined by absolute values and percentages, and quantitative data by mean and standard deviation. Qualitative variables between groups were compared using Chi- squared test. While quantitative data between groups was performed by means of t-test and ANOVA test. For all statistical tests a value of p < 0.05 will be considered statistically significant. Result: Segmental resection was associated with higher rate of severe post-operative complications in comparison with discoid resection or shaving technique (23.5% versus 5% versus 0% respectively) (p = 0.005). We showed statistical differences among the three study groups for nodule size (p < 0.001) and localization (p = 0.02). Our analysis showed statistical differences among the three groups in term of additional procedures performed at the same time of bowel surgery, in particular in case of endometriosis of the ureter (p = 0.001) and the parametrium (p = 0.04).After a long follow-up (46.4 ± 0.5 months for the group I, 42.2 ± 1.6 months for the group II, 39.7 ± 1.8 months for the group III), the shaving group was associated to higher recurrence rate (12.7%) in comparison with the discoid group (5%) and the segmental resection group (1.3%) (p = 0.01). Conclusion: We showed that segmental resection is associated with high rate of postoperative complications. Conversely, this strategy should avoid the need of further interventions in young patients. Conservative surgery, such as discoid resection and shaving, revealed a higher recurrence rate and could be more appropriate in women approximating menopause because of the lower possibility of recurrence. Keywords: Laparoscopy, Endometriosis, Colorectal resection, Shaving, Discoid resection